2018
DOI: 10.1155/2018/7456894
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breed, Gender, and Acid Stimulation in Dog Saliva Proteome

Abstract: Saliva gained interest as a potential noninvasive source of biomarkers in humans and that interest starts to be extended also to other animal species. For this purpose, the knowledge of the salivary proteome in healthy conditions and the factors that affect it and how they affect it are necessary. The aim of the present study was to assess the effect that gender and breed have in saliva proteome and the changes in it induced by stimulation with acid. Saliva from 4 different purebred dogs (Portuguese Podengo, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Besides that, in our study, there was no difference in total protein concentration between males and females. The same result was found in the study by Lucena et al [29], in which there was no major differences between genders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Besides that, in our study, there was no difference in total protein concentration between males and females. The same result was found in the study by Lucena et al [29], in which there was no major differences between genders.…”
Section: Discussionsupporting
confidence: 89%
“…The saliva collection device has no cellulose in its composition [27] and allows immediate visual confirmation of the volume of saliva obtained; the plunger compresses the absorbent pad and the saliva is collected in the Eppendorf tube portion of the device. Foremost, differently from previous studies where the collection of saliva in dogs was performed under anesthesia with stimulation with acid [28,29], we have opted for a noninvasive collection without any other stimulation mechanism or general anesthesia. However, there were difficulties regarding the sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find similar proteins to those from tumor tissues which was probably due to the different source of samples, as proteins in saliva could be either secretary proteins from zygomatic, parotid, mandibular and sublingual salivary glands or proteins from oral tumors. Compared with the previously reported normal canine salivary proteomics, a number of different proteins in the CP group were observed [1215]. This was possibly owing to different groups of dogs in the study as we combined periodontitis and healthy dogs as a CP group.…”
Section: Discussionmentioning
confidence: 70%
“…In order to discover novel salivary proteins for human oral tumors, a proteomic approach has been performed [811]. In healthy dogs, salivary proteomic analysis as well as the comparison of canine salivary proteomics with that of healthy humans have recently been reported [1215]. However, the study of salivary proteomics of dogs with oral diseases has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 83% of the detected proteins were reported previously in canine saliva using proteomic approaches [23], while 51 identified proteins have never been reported before for dog saliva. At least in part, this can be attributed to different methodologies and dog breeds used among the diverse studies, since different salivary proteomes were described in dogs of different breeds [24,25].…”
Section: Discussionmentioning
confidence: 99%